THE IMPACT OF WORK CULTURE ON THE APPARATUS WORK PERFORMANCE - Muchtar Ahmad (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Work culture has a direct positive effect on the performance of the apparatus. If the apparatus creates conducive work culture in managing the allocation of village funds, their work performances will get better as well. The study aimed to explore the impact of work culture on the apparatus work performance. This quantitative study employed a survey method with causal analysis; the subject was the apparatus in Gorontalo Regency. The study results found that the creation and improvement of work culture will increase the work performance of the apparatus in managing village allocation funds. This means that work culture is a set of values, norms, and rules that are felt by individuals. It is fostering belief based on the values believed by employees to realize the best work performance in forming a work culture that occurs when the work environment or learning organization faces problems in the organization. As a result, creating a conducive workplace culture will be the main factor determining changes in apparatus performance in planning, implementing, and evaluating work programs.